(untitled) (Global Journal of Human-Social Science, 2014)
The study investigated the effects of age, parents and teachers attitude towards aggressive and non aggressive anti social behavior of adolescents. Relevant literature that investigated the main variables of the study were examined as a theoretical bases for the study. Three hypotheses were developed as measures to examine the data that were collected for the study. A self made questionnaire titled Antisocial Behaviour Scale (ABS) was developed for the study and has content validity and reliability of 0.85. This indicated that the instrument was reliable for the study. It was administered to 100 students after a simple random sampling technique was employed. The response to the questionnaire were summarized and computed using multiple regression to test for relationship between age, parents and teachers attitude on aggressive and non-aggressive anti-social behaviour of adolescents. The study found that age, parents and teachers attitude had a significant relationship on aggressive and non-aggressive anti-social behaviour of adolescents. Recommendations were also made.